SP0143 Armful hidden telangiectasia. (12th June 2018) - Frantz, C.
Abstract : Patients with systemic sclerosis (SSc) develop a broad spectrum of vascular manifestations including the almost universal Raynaud's phenomenon, commonly digital ulceration and more rarely critical digital ischaemia. In parallel, within this very heterogeneous disease, some patients will develop vascular related organ damages leading to heart or kidney failure. In addition, SSc patients commonly exhibit telangiectasia that are visible macular, dilated superficial blood vessels. They can develop near the surface of the skin or the mucous membranes. Cutaneous telangiectasia are now included in the classification criteria and may be a marker of more aggressive vascular phenotype. Furthermore, telangiectasia can occur in the gut and promote the development of more structured damages like vascular ectasias and sometimes the very specific gastric antral vascular ectasia. All these vascular lesions induce severe and recurrent chronic iron-deficiency anaemia that can require specific local treatments to stop the bleeding. They also occur in subsets of SSc patients at risk of other SSc complications that will be highlighted in the clinical cases to be presented. Disclosure of Interest: None declared